2011
DOI: 10.1177/070674371105600403
|View full text |Cite
|
Sign up to set email alerts
|

Placebos in Clinical Practice: Comparing Attitudes, Beliefs, and Patterns of Use between Academic Psychiatrists and Nonpsychiatrists

Abstract: Controversial and ethically tenuous, the use of placebos is central to medicine but even more pivotal to psychosocial therapies. Scholars, researchers, and practitioners largely disagree about the conceptualization of placebos. While different professionals often confound the meanings of placebo effects with placebo responses, physicians continue to prescribe placebos as part of clinical practice. Our study aims to review attitudes and beliefs concerning placebos outside of clinical research. Herein we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 60 publications
6
46
0
Order By: Relevance
“…They were undertaken between 1993 and 2011 in Sweden,8 Denmark,9 Israel,10 Switzerland,11 Canada,12 New Zealand,13 Germany (two studies)4 14 and the US (four studies) 3 15–17. A total of 11 studies were published as scientific articles in peer-reviewed journals, and 1 study13 was published as a letter.…”
Section: Studies On the Use Of Placebos By Doctorsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were undertaken between 1993 and 2011 in Sweden,8 Denmark,9 Israel,10 Switzerland,11 Canada,12 New Zealand,13 Germany (two studies)4 14 and the US (four studies) 3 15–17. A total of 11 studies were published as scientific articles in peer-reviewed journals, and 1 study13 was published as a letter.…”
Section: Studies On the Use Of Placebos By Doctorsmentioning
confidence: 99%
“…It could be narrow and resemble the standard understanding of placebos in the research context: ‘… an inactive substance administered to a patient in place of a medication’ 15. Or it could be wide, as in one of the US studies16 and the Canadian study,12 which provided several alternatives for the definition of placebo. The respondents could give their own definition or choose between the following alternatives, the second of which was exactly the same as in the Danish study9: ‘(1) an intervention, that is, not expected to have an effect through a known physiologic mechanism, (2) an intervention not considered to have a ‘specific’ effect on the condition treated, but with a possible ‘unspecific’ effect, and (3) an intervention that is inert or innocuous’ 12 16…”
Section: Studies On the Use Of Placebos By Doctorsmentioning
confidence: 99%
“…They are almost as effective as antidepressants, but elicit far fewer side effects. Surveys indicated that many physicians do in fact prescribe placebos (Tilburt et al 2008;Raz et al 2011). The conventional wisdom is that for a placebo to be effective, patients must believe they are receiving active medication, which entails deception.…”
mentioning
confidence: 98%
“…Unfortunately, placebo effects are not well understood by physicians. 26 Clinicians do not usually know whether the drugs they prescribe have worked, or whether their patients have been provided enough hope to move to a spontaneous recovery. One cannot assume that when patients feel better it proves that drugs have been effective.…”
Section: Which Patients Benefit From Ads?mentioning
confidence: 99%